Best practices for graphic designers : grids and page layouts : an essential guide for understanding & applying page design principles - Graver, Amy.; Jura, Ben. (2012)
" This unique, go-to guide for designers fully details the essential layout and design skills needed to succeed in this competitive industry. With fun and practical application, it offers valuable insight into strategy and business when working in the real world with real clients, starting with basic information on layout principles before delving more deeply into theory and application on a project-by-project basis. Illustrated with real-world assignments and case studies, this guide offers a behind-the-scenes take on the entire process and steps necessary to go from concept to final outcome, including how to overcome challenges presented along the way"--
Keywords: Graphic arts -- Technique; DESIGN / Graphic Arts / General